2007
DOI: 10.1029/2006jd007333
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling of rain gauge time series by multiplicative beta cascade

Abstract: [1] This paper develops a downscaling algorithm capable of producing ensembles of rain rate time series, with integration times as short as 10 s, consistent with a time series of rain rates with integration times as long as 6 hours. The algorithm is based on a stochastic multiplicative cascade using beta distributions as the random generator. The statistics of these cascades are developed in the paper. The cascade requires two parameters at each of a geometric progression of scales. These parameters are estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…In order to correct this bias, Veneziano et al (2006) have applied an iterative estimation procedure that adjusts the parameters estimated on the dressed process so that the K(q) function of the simulated (disaggregated) series reproduces that of the observed series. Paulson and Baxter (2007) have used a similar approach, wherein, the objective function of an optimization process is the sum of the absolute differences between the second and third moments of the measured rainfall time series across the considered scales. In this study, to point out the impact of the model structure (canonical and microcanonical) on the bias of the estimates, any bias correction is applied.…”
Section: Discrete Beta-logstable (Bls) Canonical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to correct this bias, Veneziano et al (2006) have applied an iterative estimation procedure that adjusts the parameters estimated on the dressed process so that the K(q) function of the simulated (disaggregated) series reproduces that of the observed series. Paulson and Baxter (2007) have used a similar approach, wherein, the objective function of an optimization process is the sum of the absolute differences between the second and third moments of the measured rainfall time series across the considered scales. In this study, to point out the impact of the model structure (canonical and microcanonical) on the bias of the estimates, any bias correction is applied.…”
Section: Discrete Beta-logstable (Bls) Canonical Modelmentioning
confidence: 99%
“…As the bare process R b,k is not really observed, weights W can only be estimated by the reverse dressed process R k . In general, the statistics of the bare rainfall provide biased estimates of the dressed rainfall, and vice versa (e.g., Lovejoy and Schertzer, 1995;Veneziano et al, 2006;Paulson and Baxter, 2007). In order to correct this bias, Veneziano et al (2006) have applied an iterative estimation procedure that adjusts the parameters estimated on the dressed process so that the K(q) function of the simulated (disaggregated) series reproduces that of the observed series.…”
Section: Discrete Beta-logstable (Bls) Canonical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical investigation of the scaling behaviour does indeed show that not all rainfall fields obey the basic assumption that the increments of ε between scales are i.i.d. Divergences from this behaviour were described by various authors who observed that the increments were dependent on factors such as large-scale rainfall intensity (Deidda, 2000;Over and Gupta, 1994) and pixel size (Menabde et al, 1997;Over and Gupta, 1994;Paulson and Baxter, 2007). Additionally, scaling behaviour was found to differ with the intensity of storms (Venugopal et al, 2006) and thus the nonraining intervals do not scale (Olsson, 1998).…”
Section: Introductionmentioning
confidence: 94%